PERAN DOSEN UNIVERSITAS PAMULANG DALAM MENINGKATKAN PENDAPATAN USAHA UNIMART - Fithrah Kamaliyah (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This research is purposed to analyze the role of lecturer at Pamulang University in contributing from the sales revenue of Unimart so that the business can survive even in the Covid-19 pandemic. The population in this study are financial reports at Unimart Unpam in 2021, while the sample of this research is sales reports at Unimart Unpam in 2021. Data is analyzed using descriptive quantitative techniques by describing the data that has been collected, namely the ratio of lecturer purchases and reports sales of Unimart Unpam in 2021. The results of the research show that there is a fluctuating contribution of lecturers in making purchases at Unimart Unpam in 2021 even though 4881 lecturers have contributed to increasing the business income of Unimart Unpam which is one of the business units in the University of Pamulang which provides various kinds of products needs for lecturers, students, and society in general.